PS-P08-6: ESTIMATION OF TOTAL CARDIOVASCULAR RISK AMONG THE RURAL POPULATION OF BANGLADESH USING 2019 WHO CVD RISK PREDICTION NON-LABORATORY-BASED CHARTS. (January 2023) - Mamun, Mohd Abdullah Al; Bhuiyan, Mahfuzur Rahman; Sultana, Sharmin; Akhter, Jubaida; Jubayer, Shamim; Nabi, Md Noor; Sobhan, Sheikh Mohammad Mahbubus; Alim, Abdul; Milon, Sarowar Uddin; Amin, Mohammad Robed; Choudhury, Sohel Reza
Abstract : Objective: Cardiovascular disease (CVD) is the leading cause of death globally, require immediate intervention. Package of Essential Noncommunicable diseases (PEN) intervention implemented by World Health Organization in primary care of low resource setting enables healthcare workers to tailor care for patients according to their risk level, thus decrease the health care cost as well as workload of health facility. The objective of this study was to estimate the distribution of 10-year CVD risk among rural Bangladeshi adults aged > 40 years by using the 2019 WHO CVD risk prediction non-laboratory-based charts. Design and Methods: Cross-sectional, population-based study. We estimated total CVD risk using 2019 WHO CVD risk prediction non-laboratory-based charts and categorized as very low (< 5%), low (5- < 10%), moderate (10- < 20%), high (20- < 30%) and very high risk (> 30%). Participants were selected from four rural areas of two administrative districts of Bangladesh. Participants age, gender, smoking status, blood pressure, height and weight for calculation of body mass index were recorded. Participants with hypertension and moderate and high CVD risk score were referred to respective primary health care facility for further assessment and management. Results: Total of 1234 participants (male 397, female 837) were included in this study. Mean age of the participants was 54.0 years. Among the respondents 42.9%, 33.5%, 18.9% and 4.7% were in the age group of 40 to 50, 51 to 60, 61 to 70 and > 70 years respectively. Among the participants 11.9% were current smoker (men 37.1% and women 0.1%). The mean systolic and diastolic blood pressure of the participants was 134.14 and 85.03 mm of Hg respectively. The prevalence hypertension was 62%. The prevalence of hypertension was much higher among the female participants (men 53.0% and women 66.2%). Three fourth (77.6%) of the participants had CVD risk score of very low and low below (< 10%) and none had CVD score of very high risk (> 30) and one fifth (21.3%) had moderate and high CVD risk score. Among the participants with very low (< 5%), low (5–10%), moderate (10–20%) and high (20–30%) CVD risk score had 20.6%, 38.3%, 57.1% and 95.2% high blood pressure respectively. Conclusion: High prevalence of hypertension may be the main contributor of CVD score in this selected rural adult population of Bangladesh. This population require an early intervention with priority to hypertension management at community level to prevent the epidemic of the cardiovascular events.